Prevalence of vascular thrombosis and obstetric complications in systemic lupus erythematosus patients with antiphospholipid antibody - Mahaparn, Pailin; Rojnuckarin, Ponlapat (Chulalongkorn Medical Journal, 2023)
Background: The European League Against Rheumatism (EULAR) recommends primary prophylaxis with aspirin and hydroxychloroquine in systemic lupus erythematosus (SLE) patients with antiphospholipid antibodies without prior thrombosis. However, Asian populations may have lower incidence of thrombosis and the role of primary prophylaxis is unclear. Therefore, we examined the prevalence of thrombosis in Thai antiphospholipid-positive SLE patients. Methods : The medical records of SLE patients (N = 715) admitted to King Chulalongkorn Memorial Hospital from 2002 - 2012 were studied. Two hundred and eighteen patients were investigated for antiphospholipid antibodies, and 82 of them (37.6%) were positive. These 82 patients were studied for baseline characteristics, the types of antiphospholipid antibodies, prevalence of thrombosis and other potential risk factors. Results : The mean age of antiphospholipid - positive patients was 31 years, and 80.5% of them were female. The mean duration of SLE was 7.7 years, and the median follow up time was 3 years. The positive rates for lupus anticoagulant, low-titer anticardiolipin, high-titer anticardiolipin and anti-β2 glycoprotein I were 61% (50/68), 40% (33/73), 23% (19/73) and 17% (1/6), respectively. Without aspirin prophylaxis, 23 (28%) antiphospholipid-positive cases developed vascular thrombosis (24.4%) and/or obstetric complications (6.1%). Venous thrombosis was more common than arterial sites. The thrombotic rate of medium to high titer and low titer of anticardiolipin was 36.8% and 21.2%, respectively (p = 0.22). On the other hand, 2.2% (3/136) antiphospholipid-negative patients developed thrombosis or pregnancy complication with the odds ratio (OR) of 17.28 (95% confidence interval [95%CI] 5.0 - 59.8, p < 0.0001). Upon multivariate analysis in antiphospholipid-positive SLE, the age of SLE diagnosis of over 30 years and hydroxychloroquine use showed odds ratios of 2.94 (95% CI 1.02 - 8.43, p = 0.045) and 0.28 (95% CI0.08 - 0.96, p = 0.043), respectively. Conclusion : This study reveals that antiphospholipid antibodies are strong risk factors for thrombosis in patients with SLE in Thailand. Additionally, hydroxychloroquine may prevent thrombosis in these patients.